PENGARUH LABA AKUNTANSI DAN ARUS KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR OTOMOTIF YANG TERDAFTAR DI BEI PADA TAHUN 2020-2023 - Fadilah, Dwi; Sirait, Devi Ayu Putri; Tambunan, Saribulan (Gapenas Publisher, 2025)
This research aims to determine the influence of accounting profits and cash flow on share prices in automotive sector companies in 2020-2023. This research uses secondary data, secondary data is obtained from financial report data for the automotive sector registered on the IDX, namely www.idx.co.id or the respective websites in this research. Purposive sampling technique was used to take samples in this research. The population in this research is profit, steatment of changes in equity and loss reports, cash flow and annual reports of automotive sector companies listed on the IDX for 2020-2023. The data collection technique used by researchers to collect data is purposive sampling technique. The data analysis technique in research uses SPSS. The results of the research show that Accounting Profit has a significant positive effect on Share Prices, Cash Flow has a significant positive effect on Share Prices, Accounting Profit and Cash Flow have a significant positive effect on Share Prices.